State of Climate Change Adaptation and Mitigation Efforts in Agriculture for Bangladesh - Wang SW (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2011)
In many countries including south Asia, Climate Change remains a high talk low implementation phenomenon, with highly media savvy workshops and beautiful documents marred by poor implementation on the grounds. On the contrary, Bangladesh, In spite of its reputation for being poverty and disaster stricken nation with high levels of corruption has made exceptional progress in recent times. In particular the government of Bangladesh s initiatives in response to climate change (BCCSAP), food security (CIP), establishment of funding mechanisms (CCTF & BCCRF), and the creation of institutions such as climate change unit and a climate cell in all government agencies to oversee the implementation of programs and projects prescribed in BCCSAP and CIP which are now aligned into the 6th five year plans are exemplary and commendable. It was a truly gratifying experience and I remain enthused and excited with anticipation of what will come out of Bangladesh at the end of their 6th five-year plan.